Transient elastography alone and in combination with FibroTest® for the diagnosis of hepatic fibrosis in alcoholic liver disease. (29th September 2017) - Voican, Cosmin Sebastian; Louvet, Alexandre; Trabut, Jean‐Baptiste; Njiké‐Nakseu, Micheline; Dharancy, Sébastien; Sanchez, Andrea; Corouge, Marion; Lamouri, Karima; Lebrun, Amandine; Balian, Axel; Prévot, Sophie; Lachgar, Mounia; et al.
Abstract: Background & Aims: The reliability of transient elastography (TE) to assess liver fibrosis is insufficiently validated in alcoholic liver disease (ALD). We aimed to validate the diagnostic utility of TE for liver fibrosis in patients with excessive alcohol consumption and evaluate whether Fibrotest ® adds diagnostic value relative to or in combination with TE. Methods: We conducted a multicentre prospective study on a total of 217 heavy drinkers with high serum aminotransferase levels. Patients underwent liver biopsy, TE, Fibrotest ®, PGAA, APRI, FIB‐4 and FORNS. The overall diagnostic performance was evaluated by the area under the receiver operating characteristic (AUROC) curves and Obuchowski measures. Results: TE values correlated with fibrosis stage (r=.73; P <.0001) and steatosis stage (r=.19; P <.01). Patients with alcoholic hepatitis had higher TE values than those without alcoholic hepatitis ( P <.0001). In an multivariate analysis, fibrosis stage and the presence of alcoholic hepatitis were the only parameters that correlated with liver stiffness. For the diagnosis of advanced fibrosis (F≥3), the AUROC curves were 0.90, 0.85, 0.83, 0.91 and 0.90 for TE, Fibrotest ®, PGAA and associations TE‐Fibrotest ®, TE‐PGAA respectively. For the diagnosis of cirrhosis, the AUROC curves were 0.93, 0.88, 0.89, 0.94 and 0.95 respectively. The Obuchowski measures for the diagnosis of fibrosis were 0.94, 0.92, 0.91, 0.95 and 0.94 respectively. The performance of TE was not significantly different than those of Fibrotest ®, PGAA and combinations TE‐Fibrotest ®, TE‐PGAA. Conclusions: TE has excellent diagnostic value for liver fibrosis in alcoholic liver disease. The combined use of TE‐Fibrotest ® or TE‐PGAA does not improve the performance of TE.